An Experimental Swallow Evoked Potential Protocol to Investigate the Neural Substrates of Swallowing. Issue 1 (March 2020) - Kloepper, Ashley; Arnold, Joseph; Ruffolo, Alexis; Kinealy, Brian; Haxton, Chandler; Nichols, Nicole; Takahashi, Kazutaka; Lever, Teresa E.
Advancement in dysphagia intervention is hindered by our lack of understanding of the neural mechanisms of swallowing in health and disease. Evoking and understanding neural activity in response to normal and disordered swallowing is essential to bridge this knowledge gap. Building on sensory evoked potential methodology, we developed a minimally invasive approach to generate swallow evoked potentials (SwEPs) in response to repetitive swallowing induced by citric acid stimulation of the oropharynx in lightly anesthetized healthy adult rats. The SwEP waveform consisted of 8 replicable peaks within 10 milliseconds immediately preceding the onset of electromyographic swallowing activity. Methodology refinement is underway with healthy rats to establish normative SwEP waveform morphology before proceeding to models of advanced aging and age-related neurodegenerative diseases. Ultimately, we envision that this experimental protocol may unmask the pathologic neural substrates contributing to dysphagia to accelerate the discovery of targeted therapeutics.